2013
DOI: 10.1002/dc.23056
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 in imprint smears of endometrial carcinoma

Abstract: The aims of this study were to determine the expression of p53 protein in endometrial adenocarcinomas (as a potential prognostic indicator before treatment) as well as normal endometrium in imprint smears and to correlate the results with clinicopathologic parameters of primary untreated endometrial cancer patients. Two hundred fifty five patients were evaluated with endometrial imprint cytology during a 29-month period. Endometrial samples freshly resected from women who underwent total abdominal hysterectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The usefulness of the touch prep technique for diagnosis has already been demonstrated in breast cancer with 100% sensitivity and specificity in the evaluation of tumor margins at the time of the surgery [ 29 ]. This technique has also been previously used to demonstrate by immunolabeling a decreased expression of P2X7 ATP receptor in endometrial cancer cells [ 30 ] and also, recently, the relationship between p53 expression and the tumor grade [ 31 ]. However, to our knowledge, this is the first report validating the use of touch preps for enzyme activity studies, therefore opening the possibility of performing such studies in cytological samples.…”
Section: Resultsmentioning
confidence: 99%
“…The usefulness of the touch prep technique for diagnosis has already been demonstrated in breast cancer with 100% sensitivity and specificity in the evaluation of tumor margins at the time of the surgery [ 29 ]. This technique has also been previously used to demonstrate by immunolabeling a decreased expression of P2X7 ATP receptor in endometrial cancer cells [ 30 ] and also, recently, the relationship between p53 expression and the tumor grade [ 31 ]. However, to our knowledge, this is the first report validating the use of touch preps for enzyme activity studies, therefore opening the possibility of performing such studies in cytological samples.…”
Section: Resultsmentioning
confidence: 99%
“…Ki-67 expression was greater in tumors considered high grade in the cellular differentiation classifications. Other studies have found that Ki-67 expression was associated with tumor staging and histologic grading (24,25). The proliferation index, accessed by Ki-67 expression, has been considered a prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…The bile duct stump was also examined using immunohistochemical staining targeting Ki67 and p53. Ki67 is a prognostic marker of tumour proliferation that has been extensively researched in retrospective studies (22). Its cellular location is strongly cell cycle dependent (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Its cellular location is strongly cell cycle dependent (23,24). Ki67 levels are low during G1 and early S phase and peak during mitosis (22). p53 functions as a transcription factor involved in cell-cycle control, DNA repair, apoptosis and cellular stress responses (25).…”
Section: Discussionmentioning
confidence: 99%